Energy deprivation by silibinin in colorectal cancer cells: A double-edged sword targeting both apoptotic and autophagic machineries - Raina, Komal (Landes Bioscience, 2013)
Small molecules with the potential to initiate different types of programmed cell death could be useful ‘adjunct therapy’ where current anticancer modalities fail to generate significant activity due to a defective apoptotic machinery or resistance of cancer cells to the specific death mechanism induced by that treatment. The current study identified silibinin, for the first time, as one such natural agent, having dual efficacy against colorectal cancer (CRC) cells. First, silibinin rapidly induced oxidative stress in CRC SW480 cells due to reactive oxygen species (ROS) generation with a concomitant dissipation of mitchondrial potential (ΔΨ(m)) and cytochrome c release leading to mild apoptosis as a biological effect. However, with increased exposure to silibinin, cytoplasmic vacuolization intensified within the cells followed by sequestration of the organelles, which inhibits the further release of cytochrome c. Interestingly, this decrease in apoptotic response correlated with increased autophagic events as evidenced by tracking the dynamics of LC3-II within the cells. Mechanistic studies revealed that silibinin strongly inhibited PIK3CA-AKT–MTOR but activated MAP2K1/2-MAPK1/3 pathways for its biological effects. Corroborating these effects, endoplasmic reticulum stress was generated and glucose uptake inhibition as well as energy restriction were induced by silibinin, thus, mimicking starvation-like conditions. Further, the cellular damage to tumor cells by silibinin was severe and irreparable due to sustained interference in essential cellular processes such as mitochondrial metabolism, phospholipid and protein synthesis, suggesting that silibinin harbors a deadly ‘double-edged sword’ against CRC cells thereby further advocating its clinical effectiveness against this malignancy.